Thermic and chemical procedures for bronchoscopic lung volume reduction - Rötting, Matthias; Gompelmann, Daniela; Herth, Felix (Journal of thoracic disease, 2018)
In the last 14 years several endoscopic procedures have been developed to offer patients with advanced chronic obstructive pulmonary disease (COPD) and emphysema further therapeutic options, complementary to a medical treatment. In addition to the established valve implantation, new approaches have been available since 2009. These procedures include bronchoscopic thermal vapor ablation (BTVA) and polymeric lung volume reduction. Both therapies are independent of collateral ventilation (CV), are irreversible and can be used on segmental (BTVA) and sub-segmental level [polymeric lung volume reduction (PLVR)], in contrast to valve therapy. The intention is to induce a local inflammation with a following fibrosis and shrinkage and thus a volume reduction in the treated lung areas. Currently, only patients with predominant upper-lobe emphysema are treated. An improvement of lung function, exercise capacity and quality of life could be proved in RCTs for BTVA as well as for PLVR. However, the data for PLVR is very limited and has recently been available only in studies. Furthermore, the risk profile is unfavourable with a high number of adverse respiratory events. While BTVA is an established new approach, the PLVR requires re-evaluation regarding materials, predictive factors, safety profile and dosage.